Body composition changes in male and female elite soccer players: Effects of a nutritional program led by a sport nutritionist - Petri, C.; Pengue, L.; Bartolini, A.; Pistolesi, D.; Arrones, L. S. (Nutrients, 2024)
Background: Soccer is a game in constant evolution and the intensity of play is increasing. Nutrition can play a role in the physical performance of elite players, maintaining their health and facilitating recovery. It is important to cover players` energy demands, and low energy availability may therefore result in impaired performance. This study aimed to evaluate alterations in body composition to determine the effects of a nutritional program led by a sport nutritionist.